A Near‐Infrared‐II Emissive Chromium(III) Complex. (12th July 2021) - Sinha, Narayan; Jiménez, Juan‐Ramón; Pfund, Björn; Prescimone, Alessandro; Piguet, Claude; Wenger, Oliver S.
Abstract: The combination of π‐donating amido with π‐accepting pyridine coordination units in a tridentate chelate ligand causes a strong nephelauxetic effect in a homoleptic Cr III complex, which shifts its luminescence to the NIR‐II spectral range. Previously explored Cr III polypyridine complexes typically emit between 727 and 778 nm (in the red to NIR‐I spectral region), and ligand design strategies have so far concentrated on optimizing the ligand field strength. The present work takes a fundamentally different approach and focusses on increasing metal–ligand bond covalence to shift the ruby‐like 2 E emission of Cr III to 1067 nm at 77 K. Abstract : Chromium(III) polypyridyl complexes typically emit in the red or NIR‐I spectral region. We report a chromium(III) complex, which emits at 1067 nm at 77 K upon excitation at 450 nm.